2019
DOI: 10.1038/s41598-019-50490-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Visualization of Functionally Important Domains and Residues in Herpes Simplex Virus Glycoprotein K(gK) Using a Combination of Phylogenetics and Protein Modeling

Abstract: Alphaherpesviruses are a subfamily of herpesviruses that include the significant human pathogens herpes simplex viruses (HSV) and varicella zoster virus (VZV). Glycoprotein K (gK), conserved in all alphaherpesviruses, is a multi-membrane spanning virion glycoprotein essential for virus entry into neuronal axons, virion assembly, and pathogenesis. Despite these critical functions, little is known about which gK domains and residues are most important for maintaining these functions across all alphaherpesviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The inability to enter neurons abolishes the establishment and maintenance of a latent infection and thus greatly improves its safety profile. This virus, VC2, possesses a deletion of 38 amino acids in the N terminus of the viral envelope glycoprotein K (gK), which is highly conserved among all alphaherpesviruses ( 34 ). We have shown that this mutation in the N terminus of gK precludes entry by fusion and forces the virus to enter cells via endocytosis ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…The inability to enter neurons abolishes the establishment and maintenance of a latent infection and thus greatly improves its safety profile. This virus, VC2, possesses a deletion of 38 amino acids in the N terminus of the viral envelope glycoprotein K (gK), which is highly conserved among all alphaherpesviruses ( 34 ). We have shown that this mutation in the N terminus of gK precludes entry by fusion and forces the virus to enter cells via endocytosis ( 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of mutations that cause enhanced virus-induced cell fusion are found within gK mediated primarily by interactions between gK and the amino terminus of gB [ 41 , 42 , 43 , 44 ]. Together gK and UL20 are highly conserved among neurotrophic alphaherpesviruses indicating highly conserved functions within this virus family [ 45 , 46 , 47 ]. Additionally, the amino terminus of gK is required for the interaction between gB and the cellular protein Akt.…”
Section: Rational Design Of the Vc-2 Vaccinementioning
confidence: 99%
“…Although gK may not directly bind to HSV-1 receptors, overexpression of gK increases expression of 3-OS-HS, PILR alpha, nectin-1, and nectin-2 receptors and severity of corneal scarring, highlighting its role in viral pathogenesis [ 59 ]. gK is highly conserved among all neurotropic alphaherpesviruses, and thus, it is hypothesized to play important roles in neuronal infection and neuropathogenesis [ 28 ]. HSV mutant viruses overexpressing gK were reported to exacerbate mouse corneal scaring attributed at least in part to an amino-terminal 8 amino acid peptide.…”
Section: Hsv-1 Viral Glycoproteinsmentioning
confidence: 99%